Penerapan Konsep Hybrid Contract dalam Pembiayaan Rekening Koran Syariah dan Line Facility - anwarnurhasan (Program Studi Hukum Ekonomi Syariah, Institut Agama Islam Negeri Parepare, 2024)
Along with the rapid progress of the times, sharia financial institutions must be able to meet the needs of modern businesses by presenting innovative and more varied products that comply with sharia. This challenge requires practitioners, regulators, consultants, sharia councils and academics in the field of Islamic Economics to be creative in responding to these developments. The solution provided is to combine several contracts (multi contracts/hybrid contracts). This study uses a qualitative, library-based approach, namely a study based on statistics from books, articles and journals related to the topic. The analysis method is information reduction, presenting facts and drawing conclusions. The results of the study state that Islamic financial institution products that use helah and Hybrid Contracts (al-'ukud al-murakkabah) and what is the Mauamalah fiqh perspective regarding helah and hybrid contracts (al'ukud al-murakkabah) are among the concepts of Hybrid Contracts in Multi-Service Products. Application of the Hybrid Contracts Concept in Sharia Current Account and Line Facility Financing. Innovation in developing sharia products through FATWA DSN MUI hybrid contracts is a necessity to meet the need for transaction products in the sharia financial sector. Hybrid Contracts in sharia financial products receive legitimacy from FATWA DSN MUI. In implementing Hybrid contracts in multi-service product financing at Sharia Financial Institutions (LKS) generally use contract ijarah in accordance with the DSN-MUI fatwa. In this case, if LKS uses an ijarah contract, it must comply with the provisions of the fatwa as intended by the provider of services or benefits obtained from LKS.